Analytical Hierarchy Process of Instant Chocolate Drink Development based-on Consumer Preferences - Moh Wahyudin; Wagiman Wagiman; Vivi F Khulsum (APTA and DTIP FTP UGM, 2021)
Instant chocolate drink is chocolate powder in sachet packaging that has been accompanied by additional ingredients and is easy to consume. Sales competition between products has a determining factor in product selection by consumers and needs to be analyzed on factors that influence consumers to buy. This study aims to find out what are the priority attributes of decisionmaking in willingness to buy instant chocolate drinks. The method used in this research is the Analytical Hierarchy Process (AHP) approach, by arranging the problems hierarchically and then weighting and ranking priorities obtained from the results of distributing questionnaires aided by processing using the Super decision 2.0 application. Based on the results, there are seven (7) subattributes that could be influence consumers in buying an instant chocolate drink: originality taste, affordable prices, product quality, additional flavors, packaging visualization, producers of instant chocolate drink should be able to maintain the originality taste because it becomes the final factor in purchasing decisions. Beside the original taste, producers should be able to maintain affordable prices and not experience an increase in sales prices.